"Speaking truth to power: religion, caste and subaltern question in India/ edited by Manu Bhagavan and Anne Feldhaus" - "Bhagavan, Manu (ed.)" (New Delhi, 2011)
This book focuses on the role of religion and its role in the construction and deconstruction of caste and power in India.
Keywords: India